2012
DOI: 10.1128/aac.01326-12
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Activity Relationships among the Kanamycin Aminoglycosides: Role of Ring I Hydroxyl and Amino Groups

Abstract: The kanamycins form an important subgroup of the 4,6-disubstituted 2-deoxystreptamine aminoglycoside antibiotics, comprising kanamycin A, kanamycin B, tobramycin, and dibekacin. These compounds interfere with protein synthesis by targeting the ribosomal decoding A site, and they differ in the numbers and locations of amino and hydroxy groups of the glucopyranosyl moiety (ring I). We synthesized kanamycin analogues characterized by subtle variations of the 2= and 6= substituents of ring I. The functional activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 43 publications
3
39
0
1
Order By: Relevance
“…Ataluren's influence over the extent of specific tRNA selection implies that this drug's target could be the ribosome, a conclusion consistent with the drug's markedly diminished efficacy in the presence of tobramycin (Fig. 4), an aminoglycoside known to bind to the ribosome's A site (34). The apparent tRNA selection bias also suggests that both endogenous and ataluren-stimulated near-cognate tRNA mispairing are not random processes and that factors contributing to the apparent preferences are conserved.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Ataluren's influence over the extent of specific tRNA selection implies that this drug's target could be the ribosome, a conclusion consistent with the drug's markedly diminished efficacy in the presence of tobramycin (Fig. 4), an aminoglycoside known to bind to the ribosome's A site (34). The apparent tRNA selection bias also suggests that both endogenous and ataluren-stimulated near-cognate tRNA mispairing are not random processes and that factors contributing to the apparent preferences are conserved.…”
Section: Discussionmentioning
confidence: 71%
“…Taken together, these data suggest that some nonstandard base pairs are favored over others for near-cognate tRNA insertion at PTCs and that the geometry of the base pairs is the most likely determinant of this bias. significant response to ataluren if they were concurrently being treated with inhaled tobramycin, an aminoglycoside with strong affinity for the ribosomal A site (34). This observation suggested that tobramycin might be an inhibitor of ataluren's nonsense suppression activity, a possibility considered in the experiments of Fig.…”
Section: Resultsmentioning
confidence: 84%
“…In addition to promoting mistranslation, neomycin and paromomycin also negatively impact assembly of the 30S ribosomal subunit (42), although the 4,6-disubstituted aminoglycosides were not examined in this study and it is unclear if they have ever been assessed in this context. Similarly, switching the 6= substituent of ring 1 of 4,5-versus 4,6-disubstituted aminoglycosides differentially impacts ribosome inhibitory activity-replacing the 6= NH 2 group with an OH has a major negative impact on ribosome inhibition by the 4,6-disubstituted aminoglycoside kanamycin, while replacing the NH 2 of neomycin with OH (resulting in paromomycin) has a minimal impact (43). In any case, there are clearly differences in the AmgRS-responsive stress signals propagated by neomycin and paromomycin compared to the other aminoglycosides.…”
Section: Discussionmentioning
confidence: 99%
“…Several derivatives were synthesized by linking INH with another conventional drug (morpholine, 2-amino methyl pyridine, benzylamine, PAS, ciprofloxacin) by the CH fragment and evaluated for the activities. The compounds 2-Hydroxy-4-{[(isonicotinoyl hydra zono) methyl] amino}benzoic acid (19) and 1-Cyclopropyl-6-fluoro-7-{4-[(isonicotinoyl hydra zono) methyl] piperazin-1-yl}-4-oxo-1,4-dihydro quinoline-3-carboxylic acid (20) were found to possess higher activity against non-tuberculous strains than INH 62 . …”
Section: Isoniazid As Targetmentioning
confidence: 99%